Discovery and geological significance of black carbon in Triassic Yanchang Formation in Ordos Basin and its influences on source rock evaluation, NW China - Jingwei CUI; Rukai ZHU; Yang LI; Zhongyi ZHANG; Guanglin LIU; Yalin QI; Xiao HUI (Petroleum Exploration and Development)
Through investigating the Triassic Yanchang Formation in the Ordos Basin, black carbon has been found for the first time in the seventh member of the Middle Triassic Yanchang Formation (Chang 7 Member). This study suggests that the oxygen content in the East Tethys during the Middle Triassic was beyond 15% and that plants had recovered from the Late Permian mass extinction. The results show that the distribution of black carbon in the Chang 7 Member is heterogeneous in the basin. In the southeastern part, the black carbon content is the highest (possibly higher than 6%) in shale, with the proportion in total organic carbon content (TOC) up to 20%, which is lower than 10% in the northwestern and northeastern parts. The traditional practice needs to be re-evaluated when using TOC as a critical index in source rock evaluation and shale oil and gas sweet spot screening. Shale with high TOC may not necessarily be effective source rocks and or attractive targets for unconventional oil and gas exploitation, whereas those with low TOC could potentially be effective or high-quality source rocks. The TOC in shale can be divided into mass fractions of black carbon (wb), active carbon (wa), residual carbon (wr), and carbon from mature shale oil (wo). TOC-wb is recommended for evaluation of source rock, wa for screening the in-situ recovery area of low to medium maturity shale oil, and wo for appraisal of the favorable exploration area of medium to high mature shale oil. These results allow for the quantitative evaluation of organic matter composition of shale, hydrocarbon generation potential, maturation stage, and generation, expulsion and retention of shale oil, and also guide the reconstruction of climate in the source rock development period and the shale oil and gas sweet spot screening.